The roles of iPLA2, TRPM8 and TRPA1 in chemically induced cold hypersensitivity - Andersson David A; Stoakley Natalie; Gentry Clive; Bevan Stuart (SAGE Publishing, 2010)
Abstract Background The cooling agents menthol and icilin act as agonists at TRPM8 and TRPA1. In vitro, activation of TRPM8 by icilin and cold, but not menthol, is dependent on the activity of a sub-type of phospholipase A2, iPLA2. Lysophospholipids (e.g. LPC) produced by PLA2 activity can also activate TRPM8. The role of TRPA1 as a primary cold sensor in vitro is controversial, although there is evidence that TRPA1 plays a role in behavioural responses to noxious cold stimuli. In this study, we have investigated the roles of TRPM8 and TRPA1 and the influence of iPLA2 on noxious cold sensitivities in naïve animals and after local administration of menthol, icilin and LPC. The roles of the channels in cold sensitivity were investigated in mice lacking either TRPM8 (Trpm8-/-) or TRPA1 (Trpa1-/-). Results Intraplantar administration of icilin evoked a dose-dependent increase in sensitivity to a 10°C stimulus that was inhibited by iPLA2 inhibition with BEL. In contrast the cold hypersensitivities elicited by intraplantar menthol and LPC were not inhibited by BEL treatment. BEL had no effect on basal cold sensitivity and mechanical hypersensitivities induced by the TRPV1 agonist, capsaicin, and the P2X3 agonist α,β-methylene ATP. Both Trpm8-/- and Trpa1-/- mice showed longer latencies for paw withdrawal from a 10°C stimulus than wild-type littermates. Cold hypersensitivities induced by either icilin or LPC were absent in Trpm8-/- mice but were retained in Trpa1-/- mice. In contrast, cold hypersensitivity evoked by menthol was present in Trpm8-/- mice but was lost in Trpa1-/- mice. Conclusions The findings that iPLA2 inhibition blocked the development of cold hypersensitivity after administration of icilin but failed to affect menthol-induced hypersensitivity agree well with our earlier in vitro data showing a differential effect of iPLA2 inhibition on the agonist activities of these agents. The ability of LPC to induce cold hypersensitivity supports a role for iPLA2 in modulating TRPM8 activity in vivo. Studies on genetically modified mice demonstrated that the effects of icilin and LPC were mediated by TRPM8 and not TRPA1. In contrast, menthol-induced cold hypersensitivity was dependent on expression of TRPA1 and not TRPM8.